Nutritional Intake and Bone Health Among Adults With Probable Undiagnosed, Untreated Celiac Disease: What We Eat in America and NHANES 2009–2014. (17th February 2020) - Sattgast, Lara H.; Gallo, Sina; Frankenfeld, Cara L.; Moshfegh, Alanna J.; Slavin, Margaret
Abstract: Objective: The aim was to evaluate differences in nutritional intake of calcium, vitamin D, and phosphorus; serologic indices of these nutrients; and bone health among adults with and without probable, undiagnosed celiac disease (CD). Method: Cross-sectional data from What We Eat in America and the National Health and Nutrition Examination Survey 2009–2014 including self-reported dietary and supplement intake from one day of 24-hour recalls, serologic indicators, and dual x-ray absorptiometry scans were analyzed in adults with probable undiagnosed CD, who tested positive on the immunoglobulin A endomysial antibody assay (n = 48) and controls (n = 13, 634). Statistical analysis included multiple linear regression modeling controlled for age, sex, race/ethnicity, energy intake, and poverty income ratio. Results: The prevalence of probable undiagnosed CD was 1 in 285. Probable CD status was associated with a 251.6 mg (95% confidence interval [CI], 72.3–432.9) higher daily total calcium intake. The total dietary and supplement intake of those with probable CD was significantly higher in calcium density (103.4 mg/1, 000 kcal; 95% CI, 25.6–181.1) and phosphorus density (46.7 mg/1, 000 kcal; 95% CI, 3.1–90.3). Probable CD status was associated with higher dairy consumption by 0.7 cups per day (95% CI, 0.2–1.2) and higher serum phosphorus concentrations (4.0 mg/dL vs 3.8 mg/dL, p  = 0.011). No differences in serum calcium, vitamin D, or alkaline phosphatase levels were observed between groups. Probable CD status was also associated with a −0.1 g/cm 2 (95% CI, −0.2 to −0.0) lower femur bone mineral density (BMD) and a −0.1 g/cm 2 (95% CI, −0.1 to −0.0) lower femoral neck BMD. No differences in total spine BMD were observed. Conclusions: Adults with probable undiagnosed CD had lower bone density than adults without CD, despite also reporting higher total calcium intake and nutritional density of both calcium and phosphorus.